Accurate classification of major brain cell types using in vivo imaging and neural network processing - Knabbe, Johannes (Universität, 2023)
This dataset accompanies the article of the same title in the journal Plos Biology. It includes a) Ground truth datasets for the training of the StarDist neuronal network for nucleus segmentation (StardistTraining.tar.gz) b) The trained Stardist nucleus segmentation model (StardistModel.tar.gz c) raw and segmented data for the training of the cell type classification (CelltypeClassification.tar.gz, CelltypeClassificationExcInhNeurons.tar.gz) d) the raw and segmented data for the results of the paper (RawdataResults.tar.gz) e) Ground truth data for the training of all classifiers (ClassificationTrainingDataSet.tab)
Gesehen am 20.09.2023
Keywords: Forschungsdaten; Datenbank